(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The first of these three separate studies deals with the layout and contents of Celtic spindle-whorl inscriptions proposing, in particular, a new reading Kat‘te’uai for the ancient text from Parre and a new analysis for the longer text from Segeda. Object of the second study are the Celtiberian u vowels, their origins (IE inheritance, dialectal Celtic sound change, and graphic support after a velar stop) and their twofold notation, namely as <ou> in addition to normal . The third and last study explains the differ- ent sources of the palatal glides often appearing in topo- and ethnonymic forms. New analyses of several Old Celtic and Celtiberian forms are offered all through the article.